Audit Proses Perencanaan dan Implementasi Sistem Informasi PT Bank XYZ, Tbk dengan Menggunakan Cobit Framework - Iskandar, Teddy; Hermadi, Irman (Universitas Brawijaya, Indonesia, 2014)
The finance Industry develops rapidly, both Banking and Non Banking Institutions, that later this fact will bring out the competition which is getting tighter. The development is not implied not only by variety of products and finance service, but also in monetary deregulation business competency, more sophisticated finance service preferention, and Information Technology (IT) development. Based on those, IT roles, especially in Information System (IS),. As a result, the role of Information system becomes important things in supporting the banking's business and operation. It is also becoming dominant factor in winning the business competition and one way to measure IS by auditing to IS itself. IS audit that had been doing in this research was to audit IS planning and implementations process in PT. Bank XYZ, Tbk (Bank XYZ), by determining Critical Success Factor(CSF), Key Gol Indicator (KGI), Key Performance Indicator (KPI) and measuring Maturity Level by likert scale using Maturity Model in Cobit Framework. From this research, it could be concluded that all IS planning and implementations process in Bank XYZ have been conducted by right regulations as Cobit Framework and Maturity Level is placed between Level 2-Repeatable and Level 3-Defined.